Predictors of in-hospital mortality in very eldery patients presenting with acute coronary syndrome: A single-center study - Samet Yılmaz; Mehmet Koray Adalı; Oğuz Kılıç; Ayşen Til; Yalın Tolga Yaylalı; Dursun Dursunoğlu; Havane Asuman Kaftan (KARE Publishing, 2019)
Objective: Acute coronary syndrome (ACS) has become more frequent in the elderly population due to increased life expectancy. The aim of this trial was to determine clinical and laboratory factors related to in-hospital mortality in patients over 80 years of age who presented with ACS. Methods: A total 171 patients (86 men, median age 83 years) who were over 80 years of age and were hospitalized due to a diagnosis of ACS were enrolled in this study. The patients' demographic data, clinical features, and laboratory values were screened retrospectively from hospital records. Results: During the follow-up period, 19 of 171 patients (11.1%) died. The causes of death were cardiogenic shock (n=6, 31.5%), acute renal failure (n=6, 31.5%), arrhythmia (n=4, 21%), and septic shock (n=3, 15.7%). ST-segment elevation myocardial infarction presentation was more common among those who died [14 (73.7%) vs. 31 (20.5%); p<0.001]. Patients who died during in-hospital follow-up also had higher peak troponin [3.1 ng/mL (7.2) vs. 0.3 ng/mL (1.6); p<0.001] and creatine kinase-MB levels [96.7 ng/mL (194) vs. 10.9 ng/mL (36.2); p<0.001]. The results indicated that a high Global Registry of Acute Coronary Events (GRACE) risk score [odds risk (OR): 1.074, 95% confidence interval (CI): 1.039-1.110; p<0.001], ejection fraction (EF) ≤40% (OR: 8.113, 95% CI: 1.101-59.773; p=0.040), or no use of an angiotensin-converting enzyme inhibitor (ACEI)/angiotensin receptor blocker (ARB) (OR: 0.075, 95% CI: 0.006-0.995; p=0.049) was significantly associated with in-hospital mortality. Conclusion: Presentation with a high GRACE risk score, no use of an ACEI/ARB, and a low EF at admission were associated with in-hospital mortality in ACS patients more than 80 years old.